Behind our sip of tea : an ecofeminist study of environmental refugees in Kokilam Subbiah’s Mirage - R. K., Sangeetha; P., Rathna (Penerbit Universiti Kebangsaan Malaysia, 2021)
Women, in general, have been victims of so many oppressive factors such as domestic violence, gender inequalities, and patriarchal oppression in all the contexts such as personal, social, cultural, and professional. Furthermore, they often bear the brunt of natural calamities such as tsunami, famine, drought, wildfire, and hurricane and manmade disasters like war, industrialisation, urbanisation and so on, when compared to men. Many ecofeminists and researchers have studied the homogeneity between women and nature, similarity in their traits, their subjugation by the oppressive powers, and their resultant plight, under various discriminative factors such as race, caste, class, religion, culture, and colonialism. This paper aims to explore the additional challenges faced by women refugees, in particular, climate refugees as portrayed in Kokilam Subbiah’s Mirage, through the lens of ecofeminism. Throughout the novel, Kokilam Subbiah has captured the lives of women refugees through the metaphorical representation of nature. This study also attempts to underscore the parallelism between the refugee women and nature and how they are closely intertwined with each other in their victimisation and resilience and endeavours to study the veracity and universality of Warren’s premise of “naturalizing women” and “feminizing nature” with reference to the novel Mirage.